COGNITIVE GENRE PROTOTYPE MODELLING AND ITS IMPLICATIONS FOR THE TEACHING OF ACADEMIC WRITING TO LEARNERS OF ENGLISH AS A SECOND LANGUAGE - Jamilova Gulshodabonu; Ubaydullayeva Muattar Urinbekovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The teaching of academic writing to learners of English as a second language has long been preoccupied with two competing concerns: faithful reproduction of the formal conventions of established scholarly genres, and the development of learner agency  and  rhetorical  creativity.  This  paper  proposes  an  integrative  theoretical framework — Cognitive Genre Prototype Modelling (CGPM) — that draws on Eleanor Rosch’s  prototype  theory,  John  Swales’  move-step  analysis,  and  contemporary cognitive accounts of genre to reconceptualise genre knowledge as a structured mental representation  organised  around  prototypical  exemplars  rather  than  rigid  sets  of necessary  and  sufficient  features.  The  study  reports  findings  from  an  eight-week pedagogical  intervention  conducted  with  thirty  intermediate-level  ESL  learners enrolled in a university-based English for Academic Purposes (EAP) programme, and contrasts  these  outcomes  with  those  of  a  comparable  control  group  receiving conventional  genre-based  instruction.  Analytic  comparison  of  pre-  and  post-intervention texts, supplemented by questionnaire data and semi-structured interviews, indicates that learners exposed to CGPM demonstrated stronger rhetorical structuring, greater discoursal flexibility, and an enhanced metacognitive vocabulary for describing their own writing decisions. The paper concludes by outlining implications for syllabus design,  materials  development,  teacher  education,  and  the  assessment  of  academic writing in second-language settings.